A novel high-gain DC-DC converter for photovoltaic applications - Thandavarayan, Porselvi; Mouttou, Arounassalame (Bulletin of Electrical Engineering and Informatics, 2024)
This manuscript proposes a novel transformer-less, single-switch direct current (DC)-DC converter for renewable energy systems (RESs). The main aim is to solve the problems of low output voltage generated by photovoltaic (PV) arrays and discontinuous input supply current caused by switching mode power supplies. The new converter is a combination of a single-ended primary inductor, a diode/capacitor circuit, and a conventional quadratic boost converter. The main advantages are the higher rate of voltage conversion (more than 10 times for duty cycle above 50%), the diminished voltage across the active switch with diodes, and diminished gate driver necessity because of the use of a single switch with a continual input current for raising the PV panel life. Furthermore, the new converter produces low switching voltage, which improves system efficiency. The proposed converter operating principle and analysis based on steady-state performance are discussed. The proposed converter’s performance is assessed using simulation in MATLAB/Simulink, and the results were presented. A 100 W prototype model of the designed DC-DC converter is also developed, and finally, the hardware results were compared with the simulated results.